2018
DOI: 10.1089/lgbt.2017.0208
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-Free Policies and Tobacco Cessation Systems at Health Centers Serving Lesbian, Gay, Bisexual, and Transgender Clients

Abstract: Administrators at health centers serving LGBT clients viewed tobacco use as an important issue. However, there was room for improvement in implementation of systems recommended in the Guideline. Targeted outreach is warranted to improve standardization of implementation and promote cessation of tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…There are gaps in the implementation of clinical best practices by providers in LGBT-serving health centers. 30,34 In supplemental analyses (results not shown), we found that bisexual adults and sexual minority women were less likely to have health insurance. In addition, prior evidence suggests that sexual minority adults have fewer economic resources due to job selection and employment discrimination.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…There are gaps in the implementation of clinical best practices by providers in LGBT-serving health centers. 30,34 In supplemental analyses (results not shown), we found that bisexual adults and sexual minority women were less likely to have health insurance. In addition, prior evidence suggests that sexual minority adults have fewer economic resources due to job selection and employment discrimination.…”
Section: Discussionmentioning
confidence: 80%
“…For example, LGBT-serving health centers should ensure implementation of systems-level interventions to identify and connect individuals who smoke with resources for quitting. 30 Tobacco cessation media campaigns should include targeted efforts to reach sexual minorities. Comprehensive state and federal approaches should follow best practices for including and reaching sexual and gender minorities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite program facilitators' professional experience in tobacco control and services, if one has not worked directly with LGBTQ communities, the importance of having a stakeholder to serve as a program champion is magnified (Mantovani, Pizzolati, & Gillard, 2017). Even health centers who routinely provide tobacco cessation to an LGBTQ population will experience implementation barriers (Lee, DeMarco, Beymer, Shover, & Bolan, 2018), so facilitators with limited experience working with LGBTQ communities will need to develop an appropriate professional network to improve services.…”
Section: > > Implications For Practicementioning
confidence: 99%
“…These inequities may result from targeted marketing by the tobacco industry, minority stress, alcohol and/or substance co-use, and reduced access to healthcare services [ 4 9 ]. Community organizations such as nonprofits, community centers, and community health centers are prime partners for adopting and adapting evidence-based health communication campaigns for delivery among LGBTQ + communities, given their reach and trust among these groups [ 10 12 ]. They have tremendous potential for scale; a nationally representative survey found that 19% of nonprofits explicitly focus on LGBTQ + people [ 13 ] and more than 250 LGBTQ + community centers provide community-building, educational, and health services [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%